Wheat Yield Response to Nitrogen Rate Depends on Foliar Fungicide Application - R. P. Lollato; L. O. Pradella; N. Giordano; L. Ryan; L. M. Simão; J. R. Soler (Kansas Agricultural Experiment Station Research Reports, 2022)
Nitrogen (N) and fungicide are among the most important factors impacting wheat yields in Kansas. However, there is limited information on whether foliar fungicides interact with N rates in wheat yield determination. Thus, our objectives were to evaluate wheat yield as impacted by different N rates with or without the use of foliar fungicide. One field experiment was established using a factorial structure of five N rates (0, 30, 60, 90, and 120 pounds of N per acre) by two fungicide management practices (either absent or 13 fluid ounces per acre of Nexicor) in a split-plot design near Hutchinson, KS, during the 2020–2021 wheat growing season. The variety Larry was planted at 90 pounds of seed per acre, N was the whole plot and fungicide was the subplot. There was a significant interaction between N and fungicide on winter wheat grain yield, where the benefit of fungicide was greater with higher N rates. In the absence of fungicide, wheat yields ranged from 51.1 bushels per acre in the zero N rate, to 68.5 bu/a in the highest N rate. Meanwhile, grain yield ranged from 57.3 bu/a when no N was applied, to 83.8 bu/a in the highest N rate. Despite higher yields when fungicides were applied, grain yield within fungicide treatment plateaued at the 90 pounds of N per acre rate. This experiment provided initial empirical evidence for the interaction between N management and fungicide. More field experiments are expected to validate this in future years.
Keywords: wheat; nitrogen; fungicide; yield